Editorial - Vedula, Krishna (Journal of Engineering Education Transformations, 2017)
Dear Readers of JEET, We are gradually seeing the emergence of an engineering education research community in India. The papers published in JEET during the past few years are evidence of this. In particular, we have seen many high quality papers submitted to this year’s Fifth Annual Conference on Transformations in Engineering Education (ICTIEE 2018: http://ictiee.org/ictiee2018/).